From Abstract to Concrete: Designing Animated Learning Media and Olfactory Virtual Lab to Demonstrate Nose Fatigue Phenomenon in the Sensory System - Risya Pramana Situmorang; IE Johanes Juan Yutama Putra; Sefni Oemolos (Universitas Syiah Kuala, 2025)
Science education frequently encounters challenges when teaching abstract concepts like olfactory mechanisms and nose fatigue phenomena, primarily due to limitations in interactive media and practical activities. This study developed an innovative learning solution featuring integrated animated videos and a virtual laboratory to make nose fatigue concepts more tangible and interactive. Following the ADDIE framework (analysis, design, development, implementation, evaluation), our team created and validated these materials with media experts, content specialists, and educational practitioners. The validation process yielded excellent results across all quality dimensions. The animated video scored exceptionally well for its visual presentation, technical quality, and creative delivery. Similarly, the virtual laboratory earned high scientific accuracy and system stability marks. While the materials meet established educational media standards, reviewers suggested improving technical language clarity and enhancing interactivity. This research successfully bridges conceptual understanding with virtual experimentation, offering an effective approach to teaching sensory systems. The solution also accommodates content expansion for clinical applications. Ultimately, it presents a modern science learning model that addresses 21st-century educational needs, emphasizing scientific literacy and practical skill development